Ethnicity and Marginalization within the Nigerian State: A Case Study of the Nigeria Police Force - STEPHEN, OLADIPO (2013)
Following some deliberate activities of our highly celebrated past leaders and nationalists such as Nnamdi Azikwe, Chief Obafemi Awolowo and Sir Ahmadu Bello to mention but a few who fought for Nigeria independence from the colonial masters but went ahead thereafter to domesticate their loyalty to their various regions of origin. Issues of ethnicity and marginalization of the minority groups within the country have since then grown uncontrollably. In fact, the practice of ethnicity is mostly seen today in Nigeria as being normal or as being what is naturally expected of every one in position of power without which such fellow or leader risk outright rejection and castigation from his/her folk after his/her tenure in such position of authority and influence. This study therefore seeks to examine the magnitude of possible practice of ethnicity within the Nigeria Police Force through a critical review of appointments and promotion of officers to lucrative positions within the Force and factors influencing such promotions and postings since Nigeria Police Force is a model of the entire society. Keywords: Ethnicity, Marginalization, and Ethno-Political influenc